Results of limited scale trial of Sulfmonzol 5% - Enkhtogtokh, B; Burenbaatar, B (Mongolian Journal of Agricultural Sciences, 2014)
Results of experiments on the use of anthelminthic drug agianst helminths in sheep, goats and cattle reveal that preparation "Sulfmonzol 5%" has relatively higher effectiveness (98.8-100.00%) against helminths eggs in sheep and cattle at day 21 of the trial, while it is highly effective (98.1-100.0%) against goat helminths at day 14 of the trial. DOI: http://dx.doi.org/10.5564/mjas.v11i2.212 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.30-32